2021
DOI: 10.1002/jum.15629
|View full text |Cite
|
Sign up to set email alerts
|

Fetal‐TAPSE for Surveillance of Cardiac Function in Growth‐Restricted Fetuses With a Portosystemic Shunt

Abstract: Objectives Congenital portosystemic shunt (CPSS) in a growth‐restricted fetus may lead to cardiac overload and ultimately hemodynamic imbalance. The aim of the study was to describe the application of tricuspid annular plane systolic excursion (TAPSE) for surveillance of cardiac function in growth‐restricted fetuses diagnosed with CPSS. Methods The study group consisted of 7 fetuses with growth restriction diagnosed with CPSS between 2018 and 2020. Patients were followed longitudinally every 2 weeks. Sonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Abnormal shunts lead to increased cardiac preload and, thus, enlargement of the heart, which suggests that attention should be given to evaluating cardiac function in patients with IHPSS. Some researchers have proposed the potential benefit of f-TAPSE (tricuspid annular plane contraction drift) for the longitudinal monitoring of growth-restricted foetuses diagnosed concomitantly with cardiomegaly and CPSS [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal shunts lead to increased cardiac preload and, thus, enlargement of the heart, which suggests that attention should be given to evaluating cardiac function in patients with IHPSS. Some researchers have proposed the potential benefit of f-TAPSE (tricuspid annular plane contraction drift) for the longitudinal monitoring of growth-restricted foetuses diagnosed concomitantly with cardiomegaly and CPSS [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that there is an increase in TAPSE in correlation with liver shunting. 95 On the other hand, it may damage the liver parenchyma secondary to hypoxic changes that adversely regulate insulin-like growth factor-binding protein (IGFBP-1), and may result in liver dysfunction after birth. 96 Congenital intrahepatic portosystemic shunts (IPSS) are abnormal vascular communications between branches of the portal veins and the hepatic veins within the liver.…”
Section: The Fetal Adrenalsmentioning
confidence: 99%